Evaluating instructional formats and performance metrics in manual assembly task. - Ameen, Wadea; Ghaleb, Atef M; Mushtaha, Rafeek; Aburahma, Abdulaziz; Al-Ahmari, Abdulrahman (Work, 2026)
Background: Assembly is crucial in manufacturing processes, particularly with the increasing trend of customer assembly enabled by e-commerce platforms. Comprehending the importance of explicit assembly instructions is essential for improving efficiency in manual assembly activities. Objective: This study aims to assess the effect of various assembly instruction formats, particularly evaluating the role of color and text, on established performance metrics in manual assembly activities. Methods: Multiple assembly instruction formats, encompassing both colorful and non-colored images with and without textual guidance, were created and utilized in manual assembly activities. A rigorous experimental strategy was implemented, including 40 participants to evaluate assembly performance measures. Results: The study results revealed that the addition of color and text instruction has a slight effect on the performance of the assembly, but this effect isn't significant at this level of assembly complexity. Conclusion: Implementing specific assembly instruction formats can enhance performance and reduce costs, highlighting the significance of customized, explicit instructions for improved work efficiency.